Are children better witnesses than adolescents? Developmental trends in different false memory paradigms. Issue 4 (2nd October 2018) - Calado, Bruna; Otgaar, Henry; Muris, Peter
Abstract: The current study compared older children's (11/12-year-olds) and adolescents' (14/15-year-olds) vulnerability to false memory creation using two different methods (i.e., the Deese/Roediger-McDermott [DRM] and memory conformity paradigms) involving neutral and negative stimuli. In line with previous research, a developmental reversal effect was found for the DRM paradigm, which means that when employing this method children displayed lower false memory levels than adolescents. However, when using the memory conformity paradigm, the opposite pattern was found, with adolescents forming fewer false memories than children. This indicates that in a co-witness context, adolescents are less prone to memory errors than children. The emotional valence of the stimuli used in both paradigms did not notably affect the production of false memories. There was no statistically significant correlation between false memories as measured by the DRM and the memory conformity paradigms. Altogether, the current study indicates that there is no single type of false memory as different experimental paradigms evoke different types of erroneous recollections. Additionally, our study corroborates past findings in the literature concerning the issue of developmental reversal, strengthening the idea that under certain circumstances children might indeed be better witnesses than adolescents.